Planting Dates, Rates, and Methods of Agronomic Crops : SS-AGR-150/AA127, rev. 12/2019 - Wright, D.L.; Whitty, E.B.; Blount, A.R. (EDIS, 2019)
Document (table) about planting dates, seeding rates and row spacing for field and forage crops that are sexually propagated. Information for Florida that considers factors as climate and weather conditions; fertility, moisture-holding capacity, temperature, and moisture content of the soil; depth to the water table; size and germination of the seed; plant size and growth habit; growing season and water requirements of the crop; and the habits of insects, disease, and other pests.